Target Lancer - Collins, Max Allan (Collins, Max Allan. Nate Heller mystery., 2012)
Nathan Heller, 'P.I. to the Stars,' is aware of a conspiracy in the works. Heller had been involved with the Kennedys, the Mob, and the CIA in the early stages of a plan to assassinate Fidel Castro. Equipped with his knowledge, Heller realizes that he may be the one person who can prevent a high-profile political assassination. He knows all of the players; and he knows why assassins have targeted the man known to the Secret Service as 'Lancer'--John Fitzgerald Kennedy.